LINGUISTIC PROBLEMS IN LANGUAGE LEARNING - Shodiya Turgunova (Web of Journals Publishing, 2025)
This article discusses the linguistic problems confronted by students based on the written assignments. Results revealed that the students suffer from a variety of linguistic problems.
Keywords: Language, problems, lexico semantic groups; lexical means, linguistics competence.